The Effectiveness of Depression Intervention and Risk Factor in Geriatrics: a Systematic Review - Sunarti, Sri; Rakha, Muhammad; Harumbay, Nysrina; Harahap, M.; Hidayat, Rizal (Clinical and Research Journal in Internal Medicine, 2023)
Background: Increasing age is a new challenge in today's health services. With increasing age, the physiological function will decrease. Not only infectious diseases and systemic diseases, but the elderly are also prone to social problems and mental health problems, including depression. Depression is the most common mental illness in the elderly. Depression can significantly reduce the quality of life of the elderly. Aim: To obtain a deeper understanding of interventions and risk factors for depression in geriatrics.Methods: Literature searches were taken from Science Direct, Pubmed, and Google Scholar from 2020 - 2022, in which 8 eligible articles were found. The keywords used in the search were "depression", "elderly", "elder", and "geriatric". Article quality was evaluated using the CASP checklist.Results: The results of the articles were obtained from several countries. The interventions carried out can be grouped into several categories, namely interventions in the form of physical activity therapy, music therapy, psychoeducation, cognitive change, and problem-solving. This review helps inform several interventions that can be performed on the elderly and factors that support the success of interventions.Conclusion: There are several risk factors for depression in the elderly, by performing several intervention methods in the elderly, depression can reduce the risk of depression.